Spatio-temporal Responses of Arabidopsis Leaves in Photosynthetic Performance and Metabolite Contents to Burkholderia phytofirmans PsJN - Su, Fan; Gilard, Françoise; Guérard, Florence; Citerne, Sylvie; Clément, Christophe; Vaillant-Gaveau, Nathalie; Dhondt-Cordelier, Sandrine (Frontiers in Plant Science, 2016)
A valuable strategy to improve crop yield consists in the use of plant growth-promoting rhizobacteria (PGPRs). However, the influence of PGPR colonization on plant physiology is largely unknown. PGPR Burkholderia phytofirmans strain PsJN (Bp PsJN) colonized only Arabidopsis thaliana roots after seed or soil inoculation. Foliar bacteria were detected only after leaf infiltration. Since, different bacterial times of presence and/or locations in host plant could lead to different plant physiological responses, photosynthesis, and metabolite profiles in A. thaliana leaves were thus investigated following leaf, root, or seed inoculation with Bp PsJN. Only Bp PsJN leaf colonization transiently decreased cyclic electron transport and effective quantum yield of photosystem I (PSI), and prevented a decrease in net photosynthesis and stomatal opening compared to the corresponding control. Metabolomic analysis revealed that soluble sugars, amino acids or their derivatives accumulated differently in all Bp PsJN-inoculated plants. Octanoic acid accumulated only in case of inoculated plants. Modifications in vitamin, organic acid such as tricarboxylic acid intermediates, and hormone amounts were dependent on bacterial time of presence and location. Additionally, a larger array of amino acids and hormones (auxin, cytokinin, abscisic acid) were modified by seed inoculation with Bp PsJN. Our work thereby provides evidence that relative short-term inoculation with Bp PsJN altered physiological status of A. thaliana leaves, whereas long-term bacterization triggered modifications on a larger set of metabolites. Our data highlighted the changes displayed during this plant–microbe interaction to trigger physiological and metabolic responses that could explain the increase in plant growth or stress tolerance conferred by the presence of Bp PsJN.